Isolation and characterization of potential indigenous bacteria from the former bauxite mining area for heavy metal reduction - TRISNA AMELIA; LILIASARI LILIASARI; KUSNADI KUSNADI; PINGKAN ADITIAWATI (Society for Indonesian Biodiversity, 2023)
Abstract. Amelia T, Liliasari, Kusnadi, Aditiawati P. 2023. Isolation and characterization of potential indigenous bacteria from the former bauxite mining area for heavy metal reduction. Biodiversitas 24: 5096-5104. This study aimed to isolate, identify, and characterize some indigenous bacterial strains from the former bauxite mining area of Tanjungpinang, Bintan Island, Indonesia. Furthermore, this study focused on evaluating the potential of these bacteria for reducing the heavy metals lead (Pb) and chromium (Cr). The measurements of heavy metal concentrations at four sampling points, collection of soil samples as a bacteria source, and laboratory assessments for bio-removal capabilities were all conducted. Screening experiments were performed to identify bacterial strains resistant to heavy metal, using basic growth media such as Nutrient Agar (NA) and Nutrient Broth (NB) enriched with 100 ppm Pb and Cr metals. The reduction of heavy metal was analyzed with atomic absorption spectrophotometry (AAS), while the bacteria species were determined using MALDI TOF-MS. A modified version of the Kirby Bauer method was employed for toxicity reduction testing. Two bacterial strains were identified as Pb and Cr reducers and demonstrated resistance to both metals. Based on a 99.9% similarity value, the isolates were identified as Bacillus altitudinis (Isolate A) and Klebsiella pneumoniae (Isolate B), reducing Pb by approximately 72.7% and 34.5%, and Cr by 87.4% and 86.2%, respectively. The results indicated reduced toxicity in the metal-enriched media, with bacterial growth following three hours of incubation but no toxicity after 21 hours.